CONTAMINATION OF M. TUBERCULOSIS IN HOSPITAL AND OUT-OF-HOSPITAL CONDITIONS - Рогожин, А.В. (World of Medicine and Biology, 2014)
The literature review presents the main preventive measures, aimed at preventing the spread of tuberculosis, including nosocomial infections, features of the existence of Mycobacterium tuberculosis outside the body, in various environmental conditions and under the disinfectants, as well as the role of molecular genetic methods in contemporary tuberculosis epidemiology.
Keywords: tuberculosis; M. Tuberculosis; infection